Kerja Sama United Nations Fund For Population Activity Dan The National Council For Women Terkait Proyeksi Pemerintah Mesir Dalam Menghentikan Female Genital Mutilation Di Tahun 2030 - Rusdi J. Abbas; Viraya A. Khairina (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
United Nations Fund for Population Activity (UNFPA) became one of the international organizations that is active in giving aid to help social and gender issues such as Female Genital Mutilation (FGM). The Egypt government itself has made regulations related to the prohibition of FGM that clearly resulted giving the negative impact on women, such as on health sector and women's rights regarding private affairs. The presence of UNFPA and NCW is expected to be able to suppress and reduce the potential growth of FGM cases through the cooperation. With concerns related to gender inequality and misogyny, through this study, this analysis will be using the theory of liberal feminism and the International Organization Theory as the basis regarding to UNFPA – NCW’s efforts in supporting the Egyptian Government’s project to eliminate FGM in Egypt by 2030. This research will use qualitative method including document-based research and interview with Hala Yousry as the professor of rural sociology and as Vice Head of Rural Women Committee at the NCW This research is expected to be able to increase readers' awareness of the impact of FGM and how the international organizations and the country’s government combating the specific issue. Keywords: FGM, Egypt, Liberal Feminism, International Organization Theory, UNFPA, NCW